Multiculturality as an Antecedent to Work Well-being and Work Passion - Sousa, Cátia; Gonçalves, Gabriela (Journal of Tourism, Sustainability and Well-being, 2019)
Within the workplace, promoting positive feelings in regard to work well-being and work passion has become essential to an increase in health, motivation, and consequently to an increase in productivity. This study aims to assess cultural values, cultural intelligence and multicultural personality as predictors of work well-being and work passion. Based on a sample of 240 workers aged 20 to 64 years (M = 36.78, SD = 10.22), multiple linear regression was carried out. The results of the multiple linear regression analysis show that the dimensions of power distance and uncertainty avoidance have a negative influence on work well-being and work passion, whereas emotional stability is the dimension with the highest predictive value for both constructs. On the other hand, cultural intelligence has no significant predictor effect. As organisations must invest in enhancing work well-being and work passion, the identification of their predictors is of the utmost importance.